Experience and Hope for Psychosocial Nursing Care by Mothers Who Had Childbirth Difficulties in Makassar - Nurmaulid Nurmaulid; Setyowati Setyowati; Imalia Dewi Asih (Indonesian Contemporary Nursing Journal, 2016)
Introduction: Women in difficulty delivery process need a psychosocial nursing care in order to reduce their stress that in turn will affect the delivery process. The aim of this study is to identify the experience and expectation of psychosocial nursing care in women who have experienced childbirth difficulties in Makassar.Method: This research used qualitative research method. Seven women who participated in this research are selected by purposive sampling. Data are analyzed using Collaizi method.Result: Result are grouped into physical and psychological complaints during childbirth difficulties, effort to overcome complaint, family responses during childbirth difficulties, experience and perception of physical and psychosocial nursing care during childbirth difficulties, and expectation of psychosocial nursing care during childbirth difficulties. Conclusion: Variation of psychosocial nursing care is needed, in order to minimize the impact of childbirth difficulties.